A rare cause of pancytopenia: Sheehan′s syndrome - Mustafa Volkan Demir; Selçuk Yaylaci; Tuba Öztürk Demir; Tayfun Temiz; Ahmet Bilal Genç (Medical Journal of Dr. D.Y. Patil University, 2015)
Sheehan′s syndrome is characterized by varying degrees of anterior pituitary dysfunction due to postpartum ischemic necrosis of the pituitary gland after massive bleeding. Pancytopenia is rarely observed in patients with Sheehan′s syndrome. We present a patient of Sheehan′s syndrome presenting with pancytopenia. Complete recovery of pancytopenia was observed after the treatment. Clinicians should consider the possibility of hypopituitarism as a cause of pancytopenia and indicate a series of hormonal examinations. A high index of suspicion is required in women with pancytopenia for possible treatable cause like Sheehan′s syndrome.